Судьба ордынских поселений Волго-Сурского междуречья в XIV веке по нумизматическим данным - Лебедев, В.П. (Степи Европы в эпоху средневековья, 2008)
The monetary circulation of a large Golden Horde region remote from Saray including the modern right bank of the Volga between Saratov and Volgograd and Penza province is described in detail in the paper.